As Ideias antiambientais do agronegócio e a gestão bolsonarista: uma análise das políticas socioambientais no governo Bolsonaro (2019-2022) - SOUSA, Marcos Felipe Rodrigues de (Universidade Federal do Pará, 2025)
This thesis analyzes the convergences and divergences between the anti-environmental ideas of agribusiness interest groups and the socio-environmental policies formulated and implemented during the government of Jair Bolsonaro (2019 to 2022). In the presidential elections of 2018 and 2022, Bolsonaro received support from representative interest groups within the agribusiness sector, mainly due to his alignment with their ideas. Examples include the relaxation of environmental legislation and oversight, opposition to the demarcation of indigenous lands, criticism of environmental social movements, the militarization of rural areas, and the liberalization of agrochemicals, among others. Agribusiness leaders participated in the federal government, occupying high-ranking positions such as secretaries and ministers. Given this context, I conducted an analytical focus on the main representative groups of agribusiness highlighted in the literature. Among them are: the Brazilian Soybean Producers Association, the Parliamentary Front for Agriculture, the Confederation of Agriculture and Livestock of Brazil, and the Brazilian Agribusiness Association. The research employed a qualitative methodology, utilizing documentary analysis and thematic content analysis to categorize the anti-environmental ideas present in the documents of the analyzed interest groups and in the Bolsonaro government. From this analysis, the convergences and divergences of antienvironmental ideas in federal socio-environmental policies, institutional actions, and legislative projects related to Jair Bolsonaro's administration were assessed. The categories of policies analyzed included control and oversight of deforestation, anti-environmental legislative proposals from the Executive Branch, demarcation of indigenous lands, liberalization of agrochemicals, changes in environmental licensing regulations, and land tenure regulation. The theoretical analytical model used was discursive and ideational neoinstitutionalism, which considers the institutions and interests related to the ideas of political actors within a specific political, social, and institutional context. The results demonstrate that the anti-environmental ideas of agribusiness interest groups were present in the formulation and implementation of socio-environmental policies during the elections and the government of Jair Bolsonaro, particularly in anti-environmental and anti-indigenous policies. The Brazilian Soybean Producers Association and the Parliamentary Front for Agriculture showed significant convergence with the policies implemented during Bolsonaro's term, supporting his election in 2018 and 2022 and participating directly in the federal government structure. The Confederation of Agriculture and Livestock of Brazil also exhibited convergence between its anti-environmental ideas and Bolsonaro’s policies, particularly in the relaxation of environmental licensing, liberalization of agrochemicals, opposition to the demarcation of indigenous lands, and changes in land policies. The Brazilian Agribusiness Association diverged from the main agribusiness groups regarding certain anti-environmental ideas of the government and did not support Bolsonaro's election in 2018 and 2022. However, this group converged with ideas contained in specific government policies related to environmental licensing and the relaxation of agrochemical approvals, as well as being favorable to the temporal framework regarding indigenous lands. Thus, it is evident that the anti-environmental ideas of the main interest groups in Brazilian agribusiness were present during Jair Bolsonaro's administration. Through infralegal acts, appointments of agribusiness leaders, changes through normative instructions and provisional measures, budget cuts, legislative projects, and other actions, the government managed to leverage institutional conditions favorable to the antienvironmental ideas of these groups. This thesis demonstrates how specific ideas of interest groups can be implemented within a governmental administration, particularly within the Brazilian institutional context.